Co-digestion of food and garden waste with mixed sludge from wastewater treatment in continuously stirred tank reactors. (April 2016) - Fitamo, T.; Boldrin, A.; Boe, K.; Angelidaki, I.; Scheutz, C.
Highlights: Co-digestion of mixed sludge with food and garden waste enhances methane yield and productivity. The methane yield remained constant as the HRT decreased but dropped markedly when the HRT was decreased to 10 days. The productivity improved significantly in line with decreasing HRT. The trade-off between yield and productivity was achieved at 15 days HRT with stable process parameters. Abstract: Co-digestions of urban organic waste were conducted to investigate the effect of the mixing ratio between sludge, food waste, grass clippings and green waste at different hydraulic retention times (HRTs). Compared to the digestion of 100% sludge, the methane yield increased by 48% and 35%, when co-digesting sludge with food waste, grass clippings and garden waste with a corresponding % VS of 10:67.5:15.75:6.75 (R1) and 10:45:31.5:13.5 (R2), respectively. The methane yield remained constant at around 425 and 385 NmL CH4 /g VS in R1 and R2, respectively, when the reactors were operated at HRTs of 15, 20 and 30 days. However, the methane yield dropped significantly to 356 (R1) and 315 (R2) NmL CH4 /g VS when reducing the HRT to 10 days, indicating that the process was stressed. Since the methane production rate improved significantly with decreasing HRT, the trade-off between yield and productivity was obtained at 15 days HRT.